STUDI INTEGRASI TIK DALAM PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN - Wahyu Nur Hidayat; Muladi Muladi; M. Alfian Mizar (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
This study aimed to describe the perception of teachers towards the integration of ICT in learning; experience and ability to use computers in learning; availability of ICT facilities; and ICT training of teachers who have been followed. This research uses descriptive research design. Samples were taken for 166 vocational high school teachers, 53 adaptiveteachers, 38 normative teachers, and 75 productive teachers with proportionate stratified random sampling. The data collected questionnaire data, documentation studies, and interviews. The results showed that the perception of teachers towards the integration of ICT in learning included in the criteria is very high (85.51%). The ability and experience of teachers to use the computers included in the criteria is high (77.22%) and the availability of ICT facilities included in the criteria is high (75.35%). Teachers respond positively to the development of technology, basic knowledge of ICT, and has been using ICT to help the learning process. Other research results show that the intensity of training teachers in ICT included in the criteria is poor (58.5%). This type of training which have been followed by teachers, among others: a) basic computer use, b) innovative ICT-based learning, c) making the media presentation, d) the Internet, e) a word processor/script, and f) processing a number. Low intensity training taken by teachers due to the delivery of ICT training programs in schools have not been going well, so that teachers rarely get training and mentoring, especially from fellow teachers. Penelitian ini bertujuan untuk mendeskripsikan persepsi guru terhadap integrasi TIK dalam pembelajaran; pengalaman dan kemampuan menggunakan komputer dalam pembelajaran; ketersediaan fasilitas TIK; pelatihan TIK yang pernah diikuti guru. Penelitian ini menggunakan desain penelitian deskriptif. Sampel diambil sebesar 166 guru SMK, dengan rincian 53 guru adaptif, 38 guru normatif, dan 75 guru produktif dengan proportionate stratified random sampling. Data yang dikumpulkan adalah data kuesioner, studi dokumentasi, dan wawancara. Hasil penelitian menunjukkan bahwa persepsi guru terhadap integrasi TIK dalam pembelajaran masuk dalam kriteria sangat tinggi (85,51%). Kemampuan dan pengalaman guru untuk memanfaatkan komputer masuk dalam kategori baik (77,22%) dan ketersedian fasilitas TIK masuk dalam kategori baik (75,35%). Guru merespon positif terhadap perkembangan teknologi, memiliki pengetahuan dasar TIK, dan telah memanfaatkan TIK untuk membantu proses pembelajaran. Hasil penelitian lainnya menunjukkan bahwa intensitas guru dalam mengikuti pelatihan TIK masuk dalam kategori kurang baik (58,5%). Jenis pelatihan yang pernah diikuti oleh guru, antara lain (a) penggunaan komputer dasar, (b) inovasi pembelajaran berbasis TIK, (c) pembuatan media presentasi, (d) internet, (e) pengolah kata/naskah, dan (f) pengolah angka. Rendahnya intensitas pelatihan yang diikuti guru dikarenakan program penyelenggaran pelatihan TIK di sekolah belum berjalan dengan baik, sehingga guru jarang mengikuti pelatihan dan kurang mendapatkan pendampingan, terutama dari rekan sesama guru.